Determinação da ingestão alimentar e do gasto energético de ratos jovens submetidos à restrição crônica de sono - Menezes, Leticia [UNIFESP] (2017)
Sleep has been of interest to the scientific community for many years because it is a complex state that influences the functioning of the body as a whole. The use of animal models is very useful to understand the relation between insufficient sleep and the physiological, metabolic and behavioral changes. However, animal studies have raised a paradox: the concomitant presence of hyperphagia and the reduction of body weight gain. It is known that sleep restriction is a stressful factor that can induce stereotyped behavior in animals, leading to increased food spillage and not necessarily to increased food intake. It is also known that sleep deprivation / restriction can lead to increased energy expenditure. Purpose: determine the correction factor for energy intake of rats in chronic sleep restriction, considering the food spillage and evaluate the energy expenditure and body composition. Methods: male Wistar rats were divided into two groups: control (C) and restricted (R). Restricted groups were submitted to chronic sleep restriction by the single plataform method for 7, 14 and 21 days. Food intake and body weight were monitored daily. To determine the correction factor, spilled food was separated from the faeces daily. At the end of each experimental period, the animals were submitted to euthanasia to determine the energy balance and body composition. Student’s t-test was used for statistical analyses. Results: when the amount of spilled food was taken into account, restricted animals presented no significant difference in their energy intake compared to control ones. Restricted groups, despite the higher levels of metabolizable energy, presented lower fat content due to a higher energy expenditure and lower metabolic efficiency. Conclusion: it is necessary to use a correction factor for the adequate analysis of food intake of animals submitted to chronic sleep restricion, in order to avoid its overstimation due to the stereotyped behavior of gnawing. In fact, sleep restricted animals presented increased energy expenditure throughout the experimental period.